The Impacts of Digital Trade on Environmental Quality in Case of Developing Countries - Pariyar, Anita; Guo, Ping; Pan, Guoqin; Dastgeer, Awais (iRASD Journal of Economics, 2024)
Digital trade (DT) raises the incentives for developing economies, like China, India, Bangladesh, Brazil and Turkey's economic growth, to attain environmental quality, which is assessed by lowering carbon emissions, within the framework of the dual carbon targets. This study investigates the impact of DT development on carbon emissions by empirical means and their heterogeneity using panel data. Regression result shows that DT development considerably lowers the carbon emissions in the surrounding area. Utilizing its influence on upgrading industrial structure, fostering the development of green technologies, and growing economic size, DT can lower regional carbon emissions. The impact of DT on reducing carbon emissions will diminish as trade liberalization rises and carbon intensity declines. The study's conclusions are crucial from a practical perspective to effectively address climate change, achieve the carbon neutrality target, and promote better economic development.